The Integration of Dayak Deah’s Local Wisdom in Social Studies Learning within The Merdeka Curriculum at Junior High Schools in Tabalong - Syaharuddin Syaharuddin; Bambang Subiyakto; Dewicca Fatma Nadilla; Fathul Jannah (The Innovation of Social Studies Journal, 2025)
This study aims to explore the integration of Dayak Deah local wisdom values into Social Studies (IPS) instruction within the Merdeka Curriculum at public junior high schools in Tabalong Regency. The research was conducted at SMPN 1 Upau and SMPN 2 Upau, employing a qualitative case study approach. Data was collected through interviews with teachers and students, classroom observations, and analysis of relevant curriculum and syllabus documents. The results reveal that Dayak Deah local wisdom holds significant potential as a learning resource in Social Studies, yet its implementation is not fully optimized. A key challenge identified is the limited teacher knowledge of Dayak Deah local wisdom, compounded by a lack of supporting resources for its integration into teaching. These barriers impede teachers from effectively incorporating local wisdom into lessons, thereby failing to fully reflect the cultural diversity of the region. This study aims to contribute to the advancement of local wisdom-based Social Studies education and provide actionable recommendations for educators and stakeholders to enhance teacher knowledge and improve resource availability, facilitating more effective integration of local cultural values into the curriculum